Implementation of Teachers' Emotional, Moral, and Spiritual Competencies Through the Guru Penggerak Program - Khikam, Dawamul; Asrori, Asrori; Arifin, Shokhibul; Mohamoud, Mohamed Esse; Azzakiyah, Lailatul Fithriyah (STAI Publisistik Thawalib Jakarta, 2025)
The Guru Penggerak Program at the first secondary school Muhammadiyah 15 Surabaya aims to develop teachers' emotional, moral, and spiritual competencies to shape educators with holistic and high-quality character. This study seeks to describe and critically analyze strengthening teachers’ emotional, moral, and spiritual competencies by implementing the Guru Penggerak Program. Employing a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation. A thematic analysis was conducted to understand how to enhance teacher competencies. The findings reveal that the Guru Penggerak Program has significantly contributed to developing emotional, moral, and spiritual competencies among teachers. Teachers demonstrated improved emotional regulation, empathy, and the ability to foster a positive learning environment. Morally, they exhibited exemplary values such as honesty, responsibility, and justice. Their spiritual competence also improved by integrating Islamic values into the teaching and learning. The program's positive impact is reflected in enhanced teacher-student relationships, leadership styles, and a more collaborative school culture. However, challenges remain, including time constraints and limited support, which must be addressed for the program's full potential. Conclusion: The Guru Penggerak Program effectively strengthens teachers’ emotional, moral, and spiritual competencies, thereby enhancing the quality of education and character formation, despite challenges related to time and support.